Socioeconomic Burden of Community-acquired Pneumonia Associated Hospitalizations among Vietnamese Patients: A Prospective, Incidence-based Study - Quang Vo, Dr.Trung (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality. Aims: This paper presents a study that was conducted to assess the socioeconomic effects of a CAP episode to help policymakers to create effective prevention and control measures. Settings and Design: This study used an incidence-based approach from a societal perspective. Materials and Methods: The sample comprised 255 hospitalized patients at the Respiratory Department at Trung Vuong General Hospital during a 12-week period in 2017. Payment data were also collected. Results: Overall, there were 148 (58.0%) men and 107 (42.0%) female with a mean age of 66 Â± 16 years. More than half 158 (62.0%) were older than 65. The current study showed the mean treatment cost to be approximately $629 for CAP inpatients; this included direct and indirect costs. The average informal cost of treating one CAP patient was estimated at $297. On average, the biggest expenses were those related to direct medical costs - 76.6% ($481). The mean CAP-related direct non-medical and indirect costs accounted for 19.3% and 4.1%, valued at $121 and $26, respectively. The results of the study also showed a significant relationship between length of stay and average cost of treatment per CAP episode. Conclusions: The results of this study can be used to improve the allocation of resources for CAP control in Vietnam and to provide a foundation for future analyses of the cost-effectiveness of pneumococcal vaccines or other methods for controlling CAP.